A fully integrated simulation model of multi-loop aquaponics: A case study for system sizing in different environments. (May 2019) - Goddek, Simon; Körner, Oliver
Abstract: Decoupled multi-loop aquaponics systems separate the recirculated aquaculture system (RAS) and hydroponic (HP) units from each another, creating detached ecosystems with inherent advantages for both plants and fish. This gives the advantage of improved crop and fish cultivation in combination, using the minimum resource input. Up to today, the focus of aquaponics systems is mainly on fish culture and treatment of RAS effluent for optimal use in HP, and systems are designed and sized with rule of thumbs of plant growth, evapotranspiration and nutrient needs, while taking the slow responses of RAS dynamics as basis. However, in order to create the optimal fit between RAS and HP, the different systems and differences in time responses of the underlying process need to be considered. Growth of fish and plants happen in hours or days and are slow processes while photosynthesis and transpiration in crops happen in seconds or minutes and are fast processes. As in a closed loop system the main water use is due to plant transpiration, the necessary sizes of system and sub-system depend on plant transpiration. We therefore aimed at creating an aquaponics-sizing simulator based on deterministic mathematical models and thus transferrable to various circumstances with simple parameterisation. We have combined a full-scale greenhouse simulator with a possible simulation time of min 1 min including HP, greenhouse construction and physics as well as a very detailed plant energy and growth model with a model for a multi-loop aquaponics system including distillation technologies and sumps. To illustrate the quality and wide applicability of our theoretical implementation of a multi-loop aquaponics system in greenhouse conditions we made scenario simulation studies at three different climate zones as sub-arctic cold, moderate and arid subtropical regions (i.e. Faroe Islands [66°N], The Netherlands [52°N], and Namibia [22.6°S]) using the same RAS size while simulating on the fitting HP area. For sizing, we used the element P as the most valuable macronutrient for plants. We simulated in a 1-min time steps for a 3-year duration using hourly input climate data for a complete year. Results clearly indicate the importance of transpiration dynamics on system and sub-system sizing, where e.g. the optimal HP size necessary was 11, 250 m 2, 10, 250 m 2 and 5250 m 2 (tomato), or 15, 750 m 2, 14, 000 m 2 and 9250 m 2 (lettuce), for Faroe Islands, The Netherlands, and Namibia, respectively. Highlights: The sizing of decoupled multi-loop aquaponics systems is location dependent. Solar radiation is the main driver when sizing decoupled aquaponics systems. A balanced system requires different systems configurations for different climatic conditions. Numerical models are a great tool to support this complex sizing process.